Child protection: a role for conditional cash transfer programmes? - Streuli, N (Taylor and Francis, 2012)
Drawing on empirical data from a community-based study with children and adults in rural Peru, the paper analyses the everyday experiences of a conditional cash transfer programme, called Juntos. The findings show that social protection programmes like Juntos address certain child vulnerabilities by making eligibility for their cash transfers conditional on behaviour related to child protection-related such as health check-ups and school attendance. However, there are other aspects of children’s well-being that are not being considered, such as experiences of violence and exclusion. The paper discusses both opportunities and challenges for cash transfer programmes to play a greater role in child protection.